Thermal radiation effects on oscillatory squeeze flow with a particle‐fluid suspension. Issue 3 (27th October 2020) - Abbas, W.; Mekheimer, Kh. S.; Ghazy, M. M.; Moawad, A. M. A.
Abstract: The study of squeezing flow has attracted considerable interest in recent years for its important applications in industrial, biomedical and engineering domains such as fibre‐reinforced, cell squeeze technology. The aim of this study is to analyze the flow and heat transfer of a squeezed particle fluid with thermal radiation effects between parallel plates. The governing partial differentials are reduced to ordinary differential equations by a similarity transformation and solved numerically using the finite difference method. The effects of different physical parameters on the velocity and temperature profiles are discussed with the help of graphs coupled with comprehensive discussions. The results indicate that the thermal radiation parameter enhanced the fluid and particle temperature distribution and for the plate oscillation case, reverse flow is observed. To show the biological relevance of the analysis, the results obtained analyzed the influence of the squeezed artery wall on the suspension blood flow for normal and diseased blood using the experimental data from the published literature. Finally, a comparison between the present similarity solutions and previously published results shows the accuracy of the current results.